2018
DOI: 10.30984/jis.v16i2.665
|View full text |Cite
|
Sign up to set email alerts
|

The Degree Of Understanding Of Zakat On Profession/Income In Jepara Regency

Abstract: This study aimed to determine the degree of understanding of zakat on profession/income and the characteristics of the community distribution model as an effective collection model for zakat institutions. This study used a qualitative method with 68 respondents from various professional work backgrounds including civil servants, teachers, employees, military, police, and government officials. The results of this study were that Jepara people have a high degree of understanding about zakat but have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The testing on variable halal and haram aspect (A) on PTZS shows a coefficient value of 0.052 with a significance of 0.426, showing that there is no significant influence between the two variables, hence A cannot affect PTZS, primarily due to the obligation to give zakat is not considered as an essential aspect of religious compliance. Consequently, most individuals often think that the wealth they acquire is the result of their hard work, especially private sector workers (Anwar & Arifin, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The testing on variable halal and haram aspect (A) on PTZS shows a coefficient value of 0.052 with a significance of 0.426, showing that there is no significant influence between the two variables, hence A cannot affect PTZS, primarily due to the obligation to give zakat is not considered as an essential aspect of religious compliance. Consequently, most individuals often think that the wealth they acquire is the result of their hard work, especially private sector workers (Anwar & Arifin, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is written by Setianingrum and Fadhilah, 2019;Al Osaimi et al, 2016;Afriyandi, 2014;Aliyu et al, 2016;Muktiyanto and Hendrian, 2011;Romli, 2011;Siswantoro and Nurhayati, 2016. Finally, other topics was researched by Munir, 2017;Nasir, 2017;Astuti and Zulbadi, 2017;Pratama and Roziq, 2017;Sudirman and Mopoliu, 2017;Ritonga, 2017;Supriadi and Fitriani, 2017;Nurhasanah, 2018;Nababan, 2018;Itang and Azzhara, 2018;Anwar and Arifin, 2018;Triana et al, 2018;Rini, 2016;Jahar et al, 2006;Salim, 2006;Yusoff, 2006;Al Arif, 2012;Abu Bakar, 2007;Adamu and Saad, 2015;Adnan and Abu Bakar, 2009;Bidin et al, 2010;Fakhruddin, 2010;Fauziyah, 2011;Khan, 2016;Mahmud and Shah, 2009;Md Salleh, 2015;Noor and Haron, 2011;Samad and Glenn, 2010;Zamzami, 2013;Suprayitno et al, 2017;Farouk et al, 2018;Ummulkhayr et al, 2017;Saad, 2018;Rahman and Martaseli, 2018.…”
Section: Development Of Main Topics Of Zakah Research Discussionmentioning
confidence: 99%
“…The arguments for the obligation of zakat as described in the Al-Qur'an and the many hadiths showed that there are heavy demands must be carried out so that in reality is not all Muslim communities pay zakat, even though they actually know and understand the law of zakat (Anwar & Arifin, 2018). This is in line with the reality between the potential and the revenues of zakat funds (fundraising).…”
Section: Introductionmentioning
confidence: 95%